If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-2=-(1+4m)-2m
We move all terms to the left:
-2-(-(1+4m)-2m)=0
We add all the numbers together, and all the variables
-(-(4m+1)-2m)-2=0
We calculate terms in parentheses: -(-(4m+1)-2m), so:We get rid of parentheses
-(4m+1)-2m
We add all the numbers together, and all the variables
-2m-(4m+1)
We get rid of parentheses
-2m-4m-1
We add all the numbers together, and all the variables
-6m-1
Back to the equation:
-(-6m-1)
6m+1-2=0
We add all the numbers together, and all the variables
6m-1=0
We move all terms containing m to the left, all other terms to the right
6m=1
m=1/6
m=1/6
| 4(-2x+5)=28 | | 5(2d+8)=7(2d+) | | 6a-20+a(-3)=50 | | 7x2+21x-28=0 | | (9y÷14)+(3÷7)=(9÷14) | | C=x^2-5x+30 | | –6x–x+10=15–7x–5 | | 5(3x-2)+12-6x=-43 | | 5=x+4=8 | | 5(2x+8)^2=-80 | | 8x^+40x^2=O | | 3.5/h=-2 | | 5x+12x-2x=15-10 | | 3(3x+5)-12x-4=5 | | 12x+28x+15=0 | | -1x+6=x+14 | | 0.35x200=70 | | 5x+2=8x+4=15x-18 | | x2-7x-7=0 | | -1/4*7+3r=-1/8r | | 4x-7x+17=44 | | -1-(k-8)=23+k | | -3(6-10v-5v)=0 | | 4x-9=-3(x+8)-27 | | 2/3(-3x+9)=-2 | | x/13=3/5.79 | | -16x^2+185=0 | | 15/7=30/k | | -3(6-10v-5v=0 | | P2-7p-7=0 | | -8-8(-4-2n)=0 | | 2(1x+5)=16 |